COMPARATIVE STUDY BETWEEN NARBON VETCH AND COMMON VETCH IN THE SEMI-ARID REGION OF SETIF (ALGERIA) - Mahmah, Selma; Mebarkia, Amar; Rekik, Fouad (Journal of Agricultural Sciences (Belgrade), 2023)
Algeria has a limited supply of fodder. Traditional methods of raising livestock rely on the exploitation of low-quality rangelands, fallow and natural pastures with forage crops receiving little attention. The population rely on imports to meet its protein demands. Indeed, fodder production is the primary lever for improving the diet of livestock and, as a result, the productivity of the livestock systems in question. It is also crucial to the sustainability of mixed systems that combine plant and animal production. The current study was conducted to evaluate phenological stages, to analyze performances of fodder yield, grain yield and some of its components and to determine chemical composition of the species Vicia narbonensis L. in comparison with Vicia sativa L. in order to improve the fallow year in the cereal/fallow rotation and to develop the marginal lands. Trials were conducted on the plots of FERHAT Abbas University Campus under the rainfed conditions in the semi-arid region of Setif during three growing seasons (2017-2020), using 10 ecotypes of narbon vetch and 2 ecotypes of common vetch (as control ecotypes), in a randomized complete block design with three replicates. Significant effects of the ecotype, the year and the ecotype x year interaction were found, as well as a great variability in the phenological stages, agronomic characteristics and chemical composition of the ecotypes studied. A significant positive relationship (p
Keywords: fallow, chemical composition, livestock, production system, rainfed conditions, semi-arid region, Vicia narbonensis L., Vicia sativa L., yields.